Sport-Orthopädie - Schroeder J; Otte A; Reer R; Braumann KM (Dynamic Media Sales Verlag, 2015)
This paper intends to give an umbrella overview of both low back pain (LBP) management in the general population focusing on exercise therapy and specific recommendations for LBP in athletes. We have included systematic reviews and international guidelines starting from the year 2000. Among all the varying concepts, advice to stay active was most evidentlybeneficial for chronic LBP patients in general. There was strong evidencethat unspecific exercise therapy was not more effective than cognitive-behavioral concepts, and also that specific back exercises should not be advised for chronic unspecific LBP.Individually tailored and supervised exercise programs were more effective, but in general there were no differences in the efficacy of differing types of specific exercise concepts; and even classification within the pool of heterogeneous LBP syndromes and a consecutively specified exercise management did not lead to conclusive LBP management solutions. It may be proposed that future research should focus more on the problem of chronic pain in general than on unspecific back pain.For athletes,the literature mirrors an understanding of LBP, which is specific according to sports-specific demands on the back rather than on LBP which is chronic and of unknown origin. Evidence-based guideline recommendations for the management of LBP and exercises in athletes are still lacking, or merely suggested. So far, athletes suffering from chronic unspecific LBP are treated like the general population.KEY WORDS: Low Back Pain, Exercise Therapy, General Population, Athletes, Umbrella Review